Diagnostic Importance of Serum Neopterin, Procalcitonin and Some Acute Phase Proteins in Cattle with Lung Hydatid Cyst - Akyüz, E; Aydın, U; Merhan, O; Karakurt, E; Sezer, M; Batı, YU; Yıldız, U; Nuhoğlu, H; Erkılıç, EE; Ölmez, N; Özaydın, İ; Gökce, G; et al. (Journal of the Hellenic Veterinary Medical Society, 2025)
In this study, it was aimed to determine the diagnostic importance of serum neopterin, procalcitonin, and some acute phase proteins in cattle with lung hydatid cysts. In the study, 30 cattle aged 2-8 years, Simmental or crossbred, constituted the patient group, and 10 healthy cattle in the same characteristics and age range constituted the control group. The cattle were included in the study after being diagnosed with lung hydatid cyst as a result of clinical, anamnesis, auscultation, radiographic examinations, laboratory and histopathological findings. Neopterin (21.60 nmol/L) and procalcitonin concentrations (146.77 ng/L) were significantly increased in the disease group compared to the control group (respectively: 7.22 nmol/L, 47.76 ng/L) (P<0.001). Haptoglobin (P<0.001) and ceruloplasmin (P=0.047) of the acute phase proteins were higher in the patient group compared to the control group, while albumin was found to be lower (P=0.028). In conclusion, the evaluation of serum neopterin, procalcitonin, and some acute phase proteins in cattle with lung hydatid cysts was found to be important. Since hydatid disease is a zoonotic disease, it will be important to perform radiography scans and confirm the diagnosis with relevant biomarkers and take new protective measures. We think that the diagnosis will be strengthened by investigating neopterin and procalcitonin levels, especially in cattle with suspected lung cysts in radiographic findings.